North Atlantic multidecadal to centennial variability in a model and a marine proxy dataset - Mecking, Jennifer (2013)
Variability on decadal and longer timescales is of great interest in climate research due to it’s socio-economic impacts, potential for predictability and masking of anthroprogenic global warming. Observational evidence of multidecadal variability in the North Atlantic exists in the sea surface temperature (SST), often referred to as the Atlantic Multidecadal Variability (AMV), and also in the atmosphere, for example seen in sea level pressure variations associated with the North Atlantic Os- cillation (NAO). Observational oceanic data on these timescales is mainly restricted to the surface, does not extend past the last 145 years and becomes quite sparsely sampled in the higher latitudes in the earlier years. Hence, to increase our understanding of climate variability on these timescales it is essential to turn to both proxy and model data. The first part of this thesis focuses on an annually-resolved proxy record (1818- 1967) of Mg/Ca variations from a North Pacific/ Bering Sea coralline alga. Not only does the algal Mg/Ca have a very strong connection to the local winter SST and a lagged relation to the Aleutian Low it also it has a correlation of -0.87 with the winter NAO and 0.60 with the AMV index on decadal timescales. The link can explain the coherence of decadal North Pacific and AMV, as suggested by earlier studies using climate models and in the limited observational data. The second part of the thesis focuses on the ocean general circulation model, NEMO to better understand AMV. For this purpose the model was forced only with the atmospheric patterns associated with the NAO, both from the observed NAO index and from a 2000 year long white NAO index. Focusing on key ocean circulation patterns, we show that the Atlantic Meridional Overturning Circula- tion (AMOC) and sub-polar gyre (SPG) strength have a red noise response but no dominant timescale, providing no evidence for a oscillatory ocean-only mode of variability. The time derivative of both the AMOC at 30◦N and SPG strength show a strong, almost ...